Sustainable siting and design optimization of hybrid renewable energy system: A geospatial multi-criteria analysis. (1st August 2021) - Elkadeem, M.R.; Younes, Ali; Sharshir, Swellam W.; Campana, Pietro Elia; Wang, Shaorong
Graphical abstract: Highlights: A GIS-based MCDM model for the site selection of solar and wind energies in Kenya is proposed. A decision-making sizing model for sustainable energy access is developed for rural electrification. 19.28 and 35, 18.9% of Kenyan's land has the potential for installation of solar, wind, and hybrid solar/wind. Hybrid solar-wind-diesel mini-grid is the first ranked alternative for supplying the representative rural village. The designed system has the best energy, economy, and ecology performances compared to grid extension and diesel systems. Abstract: The use of hybrid renewable energy system (HRES) holds great promise for sustainable electrification and support countries reaching their energy access goals. The site selection and design of HRES are strategic stages towards ensuring an affordable, sustainable, and well-performing project. However, both are multidimensional and intricate issues that involve multiple conflicting assessment criteria and alternatives, which are not yet investigated comprehensively and simultaneously in many of the existing literature. In this context, the paper aims to develop a systematic and conceptual decision-making framework for site suitability and optimal design of HRESs, with an application on a regional scale in Kenya, Sub-Saharan Africa. The suggested framework is applied through three consecutive phases. First, a geographical information system (GIS) is combined with Best Worst Method (BWM) decision-making approach to spatially investigate and analyze the potential sites of solar, wind, and hybrid solar/wind systems. Within the spatial investigation, 9 different climatology, environment, location, and orography criteria are considered. Second, energy-economy-ecology (E3) design optimization is conducted to determine the list of feasible alternatives among grid-extension, autonomous HRES, and stand-alone diesel genset electrification schemes for powering a representative remote rural village in Kenya. Third, a post-optimality multi-criteria decision-making (MCDM) analysis is applied to decide and assess the optimal energy access design against 12 key sustainability indicators. In the third phase, the BWM is employed to define the weights of each indicator. Then, the Technique for Order Preference by Similarity to an Ideal Solution (TOPSIS) and the VIšekriterijumsko KOmpromisno Rangiranje (VIKOR) decision making approaches are used for the final ranking of feasible alternatives. The obtained site suitability maps of Kenya show that 0.91% (5322 km 2 ) and 1.5% (8828.4 km 2 ) of the land is highly suitable, 10.25% (59687 km 2 ) and 33.04% (192360 km 2 ) is suitable, and 80.5% (470313 km 2 ) and 65% (378407 km 2 ) is permanently unsuitable for establishing solar and wind systems, respectively. Also, E3-MCDM results indicate that the development of solar/wind/diesel/battery HRES is the best sustainable solution to supply the studied region as compared to other feasible alternatives. The system does not only guarantee a reliable operation with an unmet load of 552 kWh/yr, but it also has the lowest net present and energy costs at 2.6 M and 0.28 /kWh, respectively, meanwhile avoiding annual CO2 of 804 tons compared with diesel system.